Endurance training and prediction of performance in young competitive elite cyclists - Froberg, K. (1999)
A successfull junior elite cyclists must be able to obtain a high amount of oxygen pr. kg body weight in an early age, and to develop a high ventilatory capacity. It is possible to increase the ventilatory capacity more than expected if structured training is started just after puberty.